2016
DOI: 10.1172/jci.insight.87065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early cART in the gut during acute HIV infection

Abstract: Early after HIV infection there is substantial depletion of CD4+ T cells in the gastrointestinal (GI) tract lamina propria (LP), with associated epithelial barrier damage, leading to microbial translocation and systemic inflammation and immune activation. In this study, we analyzed these early events in the GI tract in a cohort of Thai acute HIV-infected patients and determined the effect of early combination antiretroviral treatment (cART). HIV-uninfected and chronically and acutely HIV-infected patients at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 68 publications
(76 reference statements)
1
44
0
1
Order By: Relevance
“…Interestingly, the AGMs actually had similar levels of neutrophils in the gut to some of the chronically infected RMs and to RMs during early acute infection [62]. Historically, it has been shown that both uninfected RMs [73] and HIV-uninfected patients [53,112] tend to have very small numbers of neutrophils resident in the gut, so their presence in AGMs suggests some role in responding to SIV infection. One possible explanation is that the resident gut neutrophils respond immediately to any possible leakage, no matter how minimal, from the gut lumen during the acute infection, through mechanisms like phagocytosis and the release of NETs [113,114].…”
Section: Plos Pathogensmentioning
confidence: 87%
“…Interestingly, the AGMs actually had similar levels of neutrophils in the gut to some of the chronically infected RMs and to RMs during early acute infection [62]. Historically, it has been shown that both uninfected RMs [73] and HIV-uninfected patients [53,112] tend to have very small numbers of neutrophils resident in the gut, so their presence in AGMs suggests some role in responding to SIV infection. One possible explanation is that the resident gut neutrophils respond immediately to any possible leakage, no matter how minimal, from the gut lumen during the acute infection, through mechanisms like phagocytosis and the release of NETs [113,114].…”
Section: Plos Pathogensmentioning
confidence: 87%
“…Although evidence exists[42], it is not currently clear whether microbial translocation occurs in hyperacute HIV infection, but studying early HIV infection requires longitudinally sampling people likely to become infected, which is ethically complicated given the demonstrated efficacy of pre-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…73 Elimination of senescent cells via senolytics-drugs that are able to push senescent cells to apoptosis-may have profound antiaging effects. 74 After the initial HIV infection, gut lymphoid tissue is decimated and recovery after ART is incomplete, 75 leading to increased translocation of microbes and microbial products that incite inflammation. Altered gut immune response is also associated with changes in the gut microbiome that may play a role in HIV-related inflammation.…”
Section: Common Pathways Of Aging: Synergies With Hiv Infectionmentioning
confidence: 99%